2019
DOI: 10.1002/ecs2.2639
|View full text |Cite
|
Sign up to set email alerts
|

Species‐specific differences in detection and occupancy probabilities help drive ability to detect trends in occupancy

Abstract: Occupancy‐based surveys are increasingly used to monitor wildlife populations because they can be more cost‐effective than abundance surveys and because they may track multiple species, simultaneously. The design of these multi‐species occupancy surveys affects statistical power to detect trends in occupancy because individual species vary in resource selection, detection probability, and rarity. We tested for differences in the ability of a large‐scale monitoring program to detect changes in single‐species oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 31 publications
2
21
0
1
Order By: Relevance
“…Conversely, estimates of occupancy had higher variability when w equaled 0.5. This was due to the variance properties of the binomial distribution where variance is highest at 0.5 and lowest near zero and one (Steenweg et al 2019). We, like other studies, found that Fig.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Conversely, estimates of occupancy had higher variability when w equaled 0.5. This was due to the variance properties of the binomial distribution where variance is highest at 0.5 and lowest near zero and one (Steenweg et al 2019). We, like other studies, found that Fig.…”
Section: Discussionsupporting
confidence: 77%
“…Thus, we had high power to detect changes in occupancy for most species in our analysis (Steenweg et al 2019). The mean time to first detection for individual species ranged from 0.9 min (95% BCI = 0.8 to 1.0, P cum = 1.0) for house wrens (Troglodytes aedon) to 7.2 min (95% BCI = 4.6 to 14.1, P cum = 0.75) for downy woodpeckers (Dryobates pubescens).…”
Section: Landbird Studymentioning
confidence: 99%
See 2 more Smart Citations
“…The burgeoning interest in making inferences about communities has led to analytical approaches that utilize data on all observed species, including bycatch species that are obtained incidentally during the course of a study that was designed with one or more focal species in mind (Iknayan et al 2014, Guillera‐Arroita 2017, Ovaskainen et al 2017, Steenweg et al 2019). While the design is optimized for the focal species, there is often information about other species readily or potentially available for extrapolation.…”
Section: Introductionmentioning
confidence: 99%